Integration of Legal Philosophy Through Manners, Ethics, Aesthetics in Intellectual Awareness - Heru Romadhon, Ahmad; Kaluku, Julisa Aprilia; Arafat, Yasser; Birahayu, Dita; Siswanto, Carissa (Universitas Negeri Gorontalo, 2025)
This study examines the role of moral, ethical, and aesthetic values in building intellectual awareness in higher education, aiming to form individuals with ethical character. With a philosophical and empirical approach, this study shows that 61.3% of respondents agree and 27.8% strongly agree with the importance of these values in the academic ecosystem. Qualitative analysis of lecturer and student interviews highlights the application of these values in academic and social interactions. This study also integrates character education with the challenges of the digital era, emphasizing the importance of digital ethics in the curriculum so that students can apply traditional values in cyberspace. These findings underline that the integration of moral, ethical, and aesthetic values not only supports moral learning but also creates graduates who are ready to contribute ethically in a dynamic global society.